Genome-wide identification of the AlkB homologs gene family, PagALKBH9B and PagALKBH10B regulated salt stress response in Populus - Zhao, Ye; Guo, Qi; Cao, Sen; Tian, Yanting; Han, Kunjin; Sun, Yuhan; Li, Juan; Yang, Qingshan; Ji, Qingju; Sederoff, Ronald; Li, Yun (Frontiers in Plant Science, 2022)
The AlkB homologs (ALKBH) gene family regulates N6-methyladenosine (m6A) RNA methylation and is involved in plant growth and the abiotic stress response. Poplar is an important model plant for studying perennial woody plants. Poplars typically have a long juvenile period of seven to ten years, requiring long periods of time for studies of flowering or mature wood properties. Consequently, functional studies of the ALKBH genes in Populus species has been limited. Based on AtALKBHs sequence similarity with Arabidopsis thaliana, 23 PagALKBHs were identified in the genome of the poplar 84K hybrid genotype (P. alba x P. tremula var. glandulosa), gene structures and conserved domains were confirmed between homologs. The PagALKBH proteins were classified into six groups based on conserved sequence compared with human, Arabidopsis, maize, rice, wheat, tomato, barley and grape. All homologs of PagALKBHs were tissue-specific; most were highly expressed in leaves. ALKBH9B and ALKBH10B are m6A demethylases and overexpression of their homologs PagALKBH9B and PagALKBH10B reduced m6A RNA methylation in transgenic lines. The number of adventitious roots and the biomass accumulation of transgenic lines decreased compared with WT. Therefore, PagALKBH9B and PagALKBH10B mediate m6A RNA demethylation and play a regulatory role in poplar growth and development. Overexpression of PagALKBH9B and PagALKBH10B can reduce the accumulation of H2O2 and oxidative damage by increasing the activities of SOD, POD and CAT, and enhanced protection for Chl a/b, thereby increasing the salt tolerance of transgenic lines. However, overexpression lines were more sensitive to drought stress due to reduced proline content. This research revealed comprehensive information about the PagALKBH gene family and their roles in growth and development and responsing to salt stress of poplar.